Screening of various raw materials and their protein concentrates: focus on alkaline extraction yields and physicochemical characterizations - Ozsoy, Bilgen; Yay, Cansu; Yellice, Alper; Biyikli, Buse; Karaalioglu, Onur; Guneser, Onur; Yuceer, Yonca (Springer, 2025)
This study comprehensively evaluated protein concentrates (PCs) obtained from diverse raw materials, including pulses, industrial by-products, and microalgal biomass, using a standardized alkaline extraction-isoelectric precipitation method. The extraction yield was highest for cold-pressed hazelnut cake (25.6%), while pea flour showed the highest protein recovery yield (77%). All PCs exhibited purities above 62%, except for microalgal PCs (similar to 57%). Spirulina biomass and sunflower meal PCs demonstrated superior solubility (> 90%) across a wide pH range (7-11). The amino acid profiles of the PCs were generally well-balanced, with the exception of low lysine and methionine levels. Notably, the PC from Schizochytrium biomass showed great potential in this regard. Aldehydes were the predominant volatile organic compounds in all PCs, particularly in pulse-based PCs. These findings provide valuable insights into the yield, purity, and functional properties of PCs from various sources, highlighting the potential of microalgal biomass and industrial by-products as sustainable protein sources for food applications.
Keywords: Alkaline extraction; Molecular weight distribution; Solubility; Volatile organic compounds; Color properties